A characterisation of mist generated from minimum quantity lubrication (MQL) compared to wet machining. (3rd December 2009) - Dasch, Jean M.; Kurgin, Sheri K.
Minimum quantity lubrication (MQL) is a new machining method in which an oil mist in a compressed air stream, rather than a flood coolant, is applied to the machining area. Three types of MQL systems exist today: external; internal, single channel; and internal, dual channel. Mist is applied differently with each type of MQL. However, the characteristics of the mist (concentration and particle size) have never been studied. Some studies have stated that MQL results in zero airborne mist levels since the oil mist either vaporises or clings to the workpiece or chips. In this research, we monitored the mist from wet fluid application and from each type of MQL system and we considered the pros and cons of each MQL type.